Production and Characterization of Insulator Material From Oil Palm Empty Fruit Bunch (EFB) - Norhaniza, Mat Saad (2012)
Malaysia is the largest producer and exporter of product based on palm oil. They are grown for the oil but only 10% will be extracted to the oil and the rest will become biomass. Based on this current situation it make oil palm empty fruit bunch (EFB) is readily available in Malaysia in large quantity. The used of landfill disposal or burning process that are become increasingly difficult due to environmental concern and legal requirement. Looking forward to a better method, an alternative approach for optimizing the usage of oil palm residues were obtained as it turn into value-added product. Focus for this study is to optimize bonding mechanism between fiber and filler and to study the effect of fiber treated on the mechanical properties and thermal decomposition. Two sets of experiment were performed, in the first set EFB fiber were blended in various ratios up to 30 wt% with the polypropylene (PP) using the twin screw extruder. For another set, 5 wt% Maleated polypropylene (MAPP) has been added to increase filler-matrix interactions and the filler dispersion in matrix. From this study, it has been proven that composite with MAPP shows the improvement on mechanical properties but as fiber loading increase the mechanical properties will be decrease due to the inefficient stress transfer. For the TGA characterization showed thermal stability for PP/EFB composite is higher with the presence of MAPP.